Crime prevention effects of data retention policies - Wolfgang Maennig; Stefan Wilhelm (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2023)
Adding to the extensive political and legal debates on data retention, this is the first study to analyse the impacts of data retention on crime prevention in Europe. Using an estimator that captures dynamic effects and is robust to heterogeneous treatment effects, we find a significant negative effect on aggregate crime rates. However, our findings indicate that a minimum of one year is required following the implementation of the obligations for a decline in crime rates to occur, indicating a gradual adjustment in delinquent behaviour. Moreover, distinct effects occur not only after the introduction of data retention laws but also when these laws are cancelled. In addition, we present evidence that the effects on aggregate crime rates are likely to be driven by changes in property crime rates and fraud, while violent crime rates remain unaffected.
Keywords: K42; K14; C21; C23; H76; 330; Crime; Anticrime politics; Data retention; Deterrence; Difference-in-Differences